Baitolo, a native shipowner's vessel, and the participation of northern Iberians in the Laietanian wine-trade under the Late Republic. (2020) - Sinner, Alejandro G.; Ferrer i Jané, Joan
Abstract : This paper discusses a unique artifact 1 of considerable archaeological, philological and historical value, as well as its implications for our understanding of the rôle that the native inhabitants of NE Spain, especially those known as the Laeetani (Plin., N H 3.3.21), played in the major economic undertaking that the export of wine from Tarraconensis in the 1st c. B.C. was to become. To do so, we first briefly describe the typological and physical characteristics of the lead stock and interpret the double Iberian inscription, baitolo, with which it was marked, probably a place-name, either that of the Ibero-Roman town of baitolo / Baetulo, which issued coins with the same legend (baitolo ) in the second quarter of the 1st c. B.C., or the name of the nearby river, the modern Besòs. 2 Subsequently, we contextualize the lead stock within the corpus of Greco-Roman lead stocks to show that no other specimen, either among stocks or any instrument or component of a ship's naval architecture, is known to have an inscription in the Iberian language. To contextualize the artifact, we will turn our attention to the native character of baitolo 's population, always from a linguistic perspective, and discuss its importance as a key centre in the wine trade. Thereafter, we make an epigraphic and archaeological re-assessment of the prior evidence for the participation of the indigenous peoples of NE Hispania in all the phases (whether land or maritime) of the chaîne opératoire that resulted in the production and commercialization of large amounts of wine for Narbonne and elsewhere. First, we reconsider all the Iberian inscriptions that have a maritime context or that can be related to the production and commercialization of wine. Second, we examine the archaeological evidence, especially shipwrecks, suggesting that Iberian-speaking individuals during the 1st c. B.C. owned ships and participated in trade by sea, an activity that can now be confirmed thanks to the new lead stock (fig. 1), which is of small dimensions (77 cm long, 11 cm high, 8 cm in width in the central box) and of modest weight (25.9 kg).